Synthesis and antitubercular activity evaluation of 4-furano-coumarins and 3-furano-chromones. Issue 18 (17th September 2018) - Singh, Ankita; Bimal, Devla; Kumar, Rajesh; Maikhuri, Vipin K.; Thirumal, M.; Senapati, Nihar Nalini; Prasad, Ashok K.
Abstract: The synthesis of novel 4-furano-coumarins and 3-furano-chromones has been achieved using silver-mediated oxidative C–H/C–H functionalization of 4-ethynylcoumarin/3-ethynylchromone with ethyl acetoacetate in 80%–90% and 82%–90% yields, respectively. The structure of the synthesized compounds was established on the basis of their spectral data analysis and the structure of one of the 4-furano-coumarins has been further confirmed on the basis of its X-ray crystallographic study. All eight synthesized 4-furano-coumarins and 3-furano-chromones exhibited moderate antitubercular activity against sensitive reference strain H37Rv of Mycobacterium tuberculosis. Graphical Abstract: